Applying newer parameter Ret‐He (reticulocyte haemoglobin equivalent) to assess latent iron deficiency (LID) in blood donors–study at a tertiary care hospital in India. Issue 7 (12th August 2018) - Tiwari, Aseem K; Bhardwaj, Gunjan; Arora, Dinesh; Aggarwal, Geet; Pabbi, Swati; Dara, Ravi C; Sachdev, Ritesh; Raizada, Arun; Sethi, Monisha
Abstract : Background: It is important to detect Latent Iron Deficiency (LID) to prevent development of an overt iron deficiency anemia. Early detection is difficult by using conventional hematological and biochemical parameters. Soluble transferrin receptor (sTfR) is presently the gold standard for diagnosing LID. We evaluated the utility of Reticulocyte Hemoglobin Equivalent (Ret‐He), a newer hematological parameter, to predict LID in blood donors as compared to sTfR. Methods: This was a randomized prospective study performed on 501 donor samples over a period of three‐months. All donors were included after administering medical history questionnaire and a brief physical examination in accordance with national guidelines (Hb ≥12.5). Additional samples were collected during donation according to the institutional standard operating procedure (SOP). All hemograms were performed on the Sysmex XE‐2100 analyzer which included Ret‐He. sTfR was measured in batch assays by ELISA (Biovendor, Czech Republic). Ret He <28 pg and sTfR≥3μg/ml were used to diagnose LID. Serum Iron, Total Iron Binding Capacity (TIBC) and Serum Ferritin were also measured simultaneously. Results: Of the 501 blood donors, sTfR and Ret‐He detected LID in 148 and 135 donors respectively. In comparison to sTfR, Ret‐He had sensitivity of 92.7%, a specificity of 97.16%, PPV of 93.1% and NPV of 96.3%. Serum Ferritin, TIBC and serum Iron had comparatively lower sensitivity of 87.16%, 79.7% and 77.7% respectively. Conclusion: Ret‐He can be used as a routine screening test to detect LID in blood donors. This could provide an opportunity to make appropriate and timely interventions like dietary changes or drug supplementation.